Design of a National-Standard Electrical Installation for a Polyclinic: A Case Study of Cibubur Hospital Polyclinic with Load, Lighting, and Backup System Analysis - Andi Galing; Erfiana Wahyuningsih (Asosiasi Dosen Muda Indonesia, 2026)
Electrical installation systems in healthcare facilities must ensure safety, reliability, and operational continuity because medical services depend on stable power supply and adequate lighting conditions. In polyclinic environments, electrical disturbances may affect service quality and patient safety, making proper system design essential. Objective: This study aims to design and evaluate the electrical installation of the Cibubur Hospital Polyclinic based on national standards, focusing on load distribution, lighting performance, backup power systems, and grounding effectiveness. Method: This research employs a mixed qualitative–quantitative descriptive approach. Data were collected through field observations, direct measurements using electrical instruments (clamp meter, lux meter, and earth tester), and documentation review of installation layouts and technical standards. The analysis was conducted through technical calculations and standard-based evaluation. Results: The total electrical load is divided into 11,883 W for normal PLN load and 7,406 W for priority UPS load, indicating a functional separation between general and critical services. Lighting measurements show that seven out of ten rooms meet the required standards, while three rooms remain below the threshold. The grounding system demonstrates resistance values well below the allowable limit, indicating effective protection performance. Implications: The results indicate that integrated electrical installation design can support safe and continuous healthcare operations, although improvements in lighting uniformity and system specification consistency are still required. Originality: This study offers an integrated evaluation of load distribution, lighting, backup power, and grounding within a single polyclinic case study, providing practical and academic contributions to electrical system design in healthcare facilities.